1985
DOI: 10.1177/030098588502200104
|View full text |Cite
|
Sign up to set email alerts
|

Encephalitozoonosis in Squirrel Monkeys (Saimiri sciureus)

Abstract: Abstract. Twenty-two cases of naturally occumng encephalitozoonosis in squirrel monkeys are reported from breeding colonies of the Delta Regional Primate Research Center, Covington, La. Characteristic foci of granulomatous inflammation and organisms were demonstrated in brains, kidneys, lungs, adrenals, and livers. Vasculitis and perivasculitis were also common lesions in several organs. At least seven cases were congenital while ten others occurred in monkeys less than nine months old. Granulomatous placentit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 16 publications
5
52
2
Order By: Relevance
“…Disseminated natural infections resulting in high morbidity and severe encephalitis caused by Encephalitozoonlike organism have been reported for stillborn and young squirrel monkeys (Saimiri sciureus) in the United States (28,337). Although parasite identification was based on electron microscopy only, which does not allow one to distinguish E. cuniculi from E. hellem, the neuropathological symptoms strongly suggested that E. cuniculi was the species involved.…”
Section: Infections In Animalsmentioning
confidence: 99%
“…Disseminated natural infections resulting in high morbidity and severe encephalitis caused by Encephalitozoonlike organism have been reported for stillborn and young squirrel monkeys (Saimiri sciureus) in the United States (28,337). Although parasite identification was based on electron microscopy only, which does not allow one to distinguish E. cuniculi from E. hellem, the neuropathological symptoms strongly suggested that E. cuniculi was the species involved.…”
Section: Infections In Animalsmentioning
confidence: 99%
“…can be transmitted transplacentally from mother to offspring (100,252). Transplacental transmission may even be important in the pathogenesis of the disease, especially in foxes, dogs, and nonhuman primates such as squirrel monkeys (137,145,252).…”
Section: Sources Of Human Infection and Transmissionmentioning
confidence: 99%
“…Four categories of host-parasite interaction have been described for mammalian and human encephalitozoonosis (192): (i) latent asymptomatic or chronic mildly symptomatic infection, known in mice and rabbits of all ages and in dogs, foxes, and squirrel monkeys infected as adults (16,45,101); (ii) acute, potentially fatal disease, observed in neonatal dogs, foxes, and squirrel monkeys (21,136,137,252); (iii) proliferation of the parasite in the absence of competent host defenses, seen in patients with cellular immunodeficiency and athymic mice in vivo and in cell cultures in vitro (81,177); and (iv) symptomatic human disease in the immunocompetent host (175 (56,194). Also, alteration of more specific immunologic responses, including enhanced killer cell activity and activation of macrophages, has been demonstrated in animals with encephalitozoonosis (142).…”
Section: Host-parasite Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abortion and stillbirth induced by E. cuniculi were reported in single cases in horses (AFIP, 1988(AFIP, , 2004Van Rensburg et al, 1991;Patterson-Kane et al, 2003) and in squirrel monkeys (Zeman and Baskin, 1985) and have been assumed in cattle (Reetz, 1995). There are only three reports on equine placentitis and abortion caused by E. cuniculi (AFIP, 1988(AFIP, , 2004Patterson-Kane et al, 2003).…”
mentioning
confidence: 99%